(untitled) (Research, Society and Development, 2022)
This study aimed to describe the importance of emotions in learning through neuropsychology. This is a bibliographic research with data collected to analyze neuropsychology in the field of emotional learning, using theoretical resources. bibliographic data, being identified on the Google Scholar, Scientific Electronic Library Online (SciELO) and Virtual Health Library (BVS) sites, aiming to collect and record, in an orderly manner, the information. It is necessary that there is a knowledge of the functionality of the emotional neurological collection as a decisive element for the moment of learning. By including such methodological strategies, it may be possible to stimulate positive emotions that are favorable to learning and that guarantee the success of individual knowledge. The emotion-learning relationship requires a delicate analysis, as the learning processes make up a web of factors that favor or hinder the success of students.